Przemiany w wojskowości chińskiej na przełomie XIX i XX w. - zarys problematyki - Nowikiewicz, Mateusz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The purpose of this article is to outline the genesis of the Chinese New Army (xinjun) and respective stages of its further development during late Qing period, as well as to highlight the factors which largely influenced the final shape of military reforms, undertaken at the turn of the 19th and 20th centuries in China
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne